Slaughterhouses fungal burden assessment: a contribution for the pursuit of a better assessment strategy - Viegas, Carla (2021)
© 2016 by the authors; licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons by Attribution (CC-BY) license (http://creativecommons.org/licenses/by/4.0/).